(untitled) (Research, Society and Development, 2020)
Objective: to understand the perceptions of individuals undergoing cancer treatment regarding the use of music in the hospital environment. Methods: descriptive and exploratory study, with a qualitative approach, conducted with 12 individuals, including adults and the elderly, hospitalized in the oncology sector in the largest public hospital in the west of the state of Santa Catarina, Brazil. Data collection took place in the first semester of 2019, through semi-structured interviews, after the musical intervention in the hospital environment. The data were organized into thematic categories and analyzed using the content analysis method. Thus, three categories emerged: 1) Hospitalization and its implications for the lives of individuals; 2) Concept of health and health promotion in the face of the hospitalization process; and 3) Music as a health promotion tool. Results: hospitalization is a difficult, remarkable process that can be traumatic. Music, as a health promotion strategy, allows for distraction, reduction of stress and anxiety, providing significant effects, such as joy, inner peace and distraction for hospitalized people. Conclusion: from the perceptions of hospitalized individuals, it can be understood that music contributes to the promotion of health in the hospital environment, as it awakens different sensations and meanings, contributing to a less difficult hospitalization process. It also strengthens the bond between professionals, hospitalized individuals and their families, contributing to the humanization of care for people undergoing cancer treatment.